Beyond disciplinary boundaries: Educational codesign and body percussion in the changing school - Mazzella, Mariapia; Ambretti, Antinea (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
In an educational context increasingly focused on the complexity and interconnectedness of knowledge, interdisciplinary teaching emerges as an effective response to promoting meaningful and inclusive learning. This paper presents an action research experience conducted in a preschool and primary school, through an interdisciplinary music workshop based on codesign between teachers from different areas: music, motor skills, linguistics, mathematics, art, and imagery. Analysis of the questionnaires administered to teachers revealed a small increase in their willingness to cooperate, although considerable resistance remained. The study is exploratory in nature, aimed at understanding collaborative dynamics and teacher cohesion without generalizing its effects. Considering these findings, we propose introducing Body Percussion among adults as a physical practice to improve empathy, listening, and psychophysical wellbeing within working groups. The project subsequently suggested the use of Body Percussion as a musicalmotor activity to foster cohesion among teachers. The activity is sustainable not only methodologically, thanks to the flexibility of the resources employed, but also relationally, facilitating the resolution of initial conflicts among teachers and progressively improving the collaborative climate. The research takes a reflective and exploratory perspective, investigating how disciplinary, interdisciplinary, and transdisciplinary approaches can interact in an educational process centered on shared responsibility and the holistic development of the individual. The integration of knowledge, in fact, not only enriches teaching but represents a strategic lever for addressing global challenges and developing critical, creative, and collaborative citizens capable of navigating disciplinary boundaries and building shared knowledge.